On the move to meaningful internet systems : OTM 2016 Conferences : Confederated International Conferences: CoopIS, C & TC, and ODBASE 2016, Rhodes, Greece, October 24-28, 2016, Proceedings /: OTM 2016 Conferences : Confederated International Conferences: CoopIS, C & TC, and ODBASE 2016, Rhodes, Greece, October 24-28, 2016, Proceedings. (2016) - Unknown
No abstract available